2012
DOI: 10.1007/s00701-012-1333-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of timing of cranioplasty in patients with large cranial defects after decompressive hemicraniectomy

Abstract: Our study suggests that many patients with large cranial defects after decompressive craniectomy can safely undergo cranioplasty in an early stage; direct answers to these questions of timing of cranioplasty are best addressed by prospective studies. Nevertheless, the present study provides a basis for decision-making in certain patients and for the design of future investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 30 publications
2
44
0
4
Order By: Relevance
“…There is no study however, that examines the effect of timing on the clinical outcome of patients. In accordance with the available literature, timing does not influence complications, but there might be an advantage for early reinsertion (<3 months), especially with respect to the risk for infections [51,52,53,54,55,56]. Recently published studies reported an approximate overall complication rate of up to 35% [51,52].…”
Section: Surgical Treatmentsupporting
confidence: 61%
“…There is no study however, that examines the effect of timing on the clinical outcome of patients. In accordance with the available literature, timing does not influence complications, but there might be an advantage for early reinsertion (<3 months), especially with respect to the risk for infections [51,52,53,54,55,56]. Recently published studies reported an approximate overall complication rate of up to 35% [51,52].…”
Section: Surgical Treatmentsupporting
confidence: 61%
“…Once the neurological and medical states of the patient have been stabilized, bone grafting is performed for esthetic, but also therapeutic, reasons and is associated with postoperative neurological improvement. 1,3,[7][8][9][11][12][13]16,22,24,27 Compared with other neurosurgical interventions, the complication rate of cranioplasty after decompressive craniectomy is surprisingly high, with a reoperation rate for wound infection, rebleeding, and wound-healing problems of up to 36.5%. 23,26 Long-term complications after autograft implantation have become an increasing concern in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons of large cranial defects after decompressive craniectomy include brain injury, cerebral infarction, subarachnoid hemorrhage and ICH (Table 1). Archavlis [4] grouped research date into three groups: <7 weeks, 7-12 weeks, and >13 weeks. Because both the first two groups are under 3 months, we combined the first two groups into one group to compare with the other group.…”
Section: Search Strategymentioning
confidence: 99%